Islamic Value-Based Entrepreneurship: Integrating Sharia Business Ethics into SMEs - Prawinda Mutiara Qalbu; Rinda Asytuti; Amrina Rosyada; Septiyani Wulandari (Jurnal Kewirausahaan dan Bisnis, 2026)
The rapid growth of micro, small, and medium enterprises (MSMEs) in Indonesia has not been fully accompanied by the internalization of ethical values in business practices, as issues such as lack of transparency and profit only orientation remain prevalent. This study aims to examine the conceptual foundations of Islamic business ethics in entrepreneurship, formulate an integration model of Islamic values in MSME operations, and analyze the impacts, challenges, and prospects of sharia-based MSME development in Indonesia. The method employed is a literature review with a descriptive-qualitative approach, drawing on various scientific journals, books, and research reports as secondary data. The findings indicate that the five core principles of Islamic business ethics tawhid, justice, free will, responsibility, and honesty can be comprehensively integrated across the production, financial, marketing, service, and social responsibility aspects of MSMEs. Consistent application of these principles has proven effective in building long-term customer trust and loyalty while enhancing business competitiveness. Despite ongoing challenges such as low sharia economic literacy and limited access to Islamic financing, the prospects for sharia-based MSMEs remain highly promising amid growing public halal awareness and digital transformation support. Integrating Islamic business ethics into MSMEs is not merely a moral choice, but an effective business strategy for achieving sustainable and high-value enterprises.